RGD-PEG-PLA Delivers MiR-133 to Infarct Lesions of Acute Myocardial Infarction Model Rats for Cardiac Protection - Bixi Sun; Shuwen Liu; Rubin Hao; Xinyue Dong; Lanbo Fu; Bing Han (MDPI AG, 2020)
Studies have shown that microRNA-133 (miR-133) plays a positive role in the growth of cardiac myocytes, the maintenance of cardiac homeostasis, and the recovery of cardiac function, which is of great significance for the recovery of acute myocardial infarction. However, the delivery of miRNA to the site of action remains a challenge at present. The purpose of this study was to design an ideal carrier to facilitate the delivery of miR-133 to the infarct lesion for cardiac protection. A disease model was constructed by ligating the left anterior descending coronary artery of rats, and polyethylene glycol (PEG)-polylactic acid (PLA) nanoparticles modified with arginine-glycine-aspartic acid tripeptide (RGD) carrying miR-133 were injected via the tail vein. The effects of miR-133 were evaluated from multiple perspectives, including cardiac function, blood indexes, histopathology, and myocardial cell apoptosis. The results showed that RGD-PEG-PLA maintained a high level of distribution in the hearts of model rats, indicating the role of the carrier in targeting the heart infarction lesions. RGD-PEG-PLA/miR-133 alleviated cardiac histopathological changes, reduced the apoptosis of cardiomyocytes, and reduced the levels of factors associated with myocardial injury. Studies on the mechanism of miR-133 by immunohistochemistry and polymerase chain reaction demonstrated that the expression level of Sirtuin3 (SIRT3) was increased and that the expression of adenosine monophosphate activated protein kinase (AMPK) decreased in myocardial tissue. In summary, the delivery of miR-133 by RGD-PEG-PLA carrier can achieve cardiac lesion accumulation, thereby improving the cardiac function damage and reducing the myocardial infarction area. The inhibition of cardiomyocyte apoptosis, inflammation, and oxidative stress plays a protective role in the heart. The mechanism may be related to the regulation of the SIRT3/AMPK pathway.